Study on Administration of Placental Extract for Pain and Quality of Life in Patients with Fibromyalgia Syndrome - Park, Kyeong Mee; Cho, Tae Hwan; Cho, Dong Pill (New Frontiers in Medicine and Medical Research Vol. 17, 2021)
Fibromyalgia syndrome (FMS) is a condition characterized by chronic widespread pain and fatigue which brings about a serious fall of quality of life in patients. Patients with FMS utilize complementary and alternative medicine therapies in addition to conventional medicine therapies. Placental extract (PE) has been used to treat fatigue, growth retardation, and pain-suffering in Korea. Yet, there is no attempt to investigate the effect of PE on the treatment of FMS. This study evaluated the effectiveness of PE administration on pain and life quality in patients with FMS. In acupuncture point injection (API) with PE, 64 patients at the clinic being treated for FMS, were retrospectively evaluated. After APIs with PE for five weeks, pain and sleep discomfort were substantially decreased. Patients also displayed elongated productive times which denote workable hours to maintain daily activity without pain-evoked break after API treatments. In another route of PE administration, a 46-year-old woman with FMS was treated intravenously with PE-containing 5% glucose solution once a week for 9 weeks. She experienced significantly improved fatigue, pain, and health-related quality of life by the successive intravenous administration of PE. The treatment effect of PE was parallel with the fatigue reduction. Data presented that both PE administrations were effective for pain control and fatigue relief in FMS. We suggest that PE is a safe and promising treatment material for FMS.